AN ANALYSIS OF DESCRIPTIVE TEXTS IN ENGLISH TEXTBOOK USING TRANSITIVITY SYSTEM - Anggun, Shafira Khairina (2016)
The main focus of the study is to investigate to what extent the descriptive texts in English textbook meet its criteria in terms of purposes, schematic structures and linguistic features. A qualitative case study method with document analysis technique is employed as the method of the study. The study also applied Systemic Functional Linguistics framework proposed mainly by M.A.K. Halliday, yet the study had focused on Transitivity system in analyzing descriptive texts. The prime data of the study were four descriptive texts of reading passages from four different chapters of an English textbook which have implemented 2013 Curriculum. The data analysis was done by examining social purposes, schematic structures and linguistics features (mainly Transitivity system). The findings showed that in terms of social purpose, three out of four descriptive texts met the purpose of descriptive text. In terms of schematic structure, one text met the criteria as descriptive text included personal comment; two texts met the criteria of descriptive text but did not include personal comment; and the last one did not meet the criteria of descriptive text. Moreover, in terms of linguistic features, only two of four descriptive texts had closely followed the linguistic features of descriptive text. However, it can be concluded that some descriptive texts in the textbook entitled "Bahasa Inggris for Senior High School Grade X" were unsatisfactory in which they were not satisfy the criteria of descriptive text. ;---Fokus utama dari penelitian ini adalah untuk menginvestigasi sejauh mana deskriptif teks yang terdapat pada buku pelajaran mencapai kriterianya, dalam hal tujuan, struktur skematik dan unsur kebahasaan. Studi kasus kualitatif dengan teknik analisis dokumen digunakan sebagai metode penelitian. Penelitian ini juga mengaplikasikan kerangka linguistik sistemik fungsional yang dicetus oleh M.A.K Halliday, tetapi penelitian ini berfokus pada sistem Transitivitas dalam menganalisis teks deskriptif. Data utama dalam penelitian ini adalah empat buah teks deskriptif dari bahan bacaan yang terdapat pada empat bab yang berbeda dalam buku pelajaran yang mengimplementasi Kurikulum 2013. Analisis data dilakukan dengan menelaah tujuan social, struktur skematik dan unsur kebahasaan (terutama Sistem Transitivitas). Hasil temuan menunjukkan bahwa dalam hal tujuan sosial, hanya tiga dari empat teks yang mencapai tujuan dari teks deskriptif. Dalam hal struktur skematik, salah satu teks mencapai kriteria sebagai teks deskriptif dengan menyertakan komentar personal; dua teks mencapai kriteria teks deskriptif tanpa menyertakan komentar personal; dan satu teks terakhir tidak mencapai kriteria teks deskriptif. Tambahan pula, dalam hal unsur kebahasaan, hanya dua teks yang yang memiliki unsur kebahasaan yang sesuai dengan unsur kebahasaan teks deskriptif. Dapat disimpulkan bahwa beberapa teks deskriptif yang terdapat pada buku pelajaran berjudul "Bahasa Inggris untuk Sekolah Menengah Atas Kelas X" tidak memuaskan dalam hal tidak memuaskan kriteria teks deskriptif.